POTRET KEPEMIMPINAN TRANSFORMASIONAL SEKOLAH DI SMA NEGERI 1 SUMBERREJO, BOJONEGORO - Ula, Laili Rohmatul (Paradigma, 2021)
Leadership is an ability or strength within a person to lead and influence others in terms of work. In leadership education, what is needed today is a leader who has a basis in cultural and religious values who will be able to anticipate all problems and changes that occur in the world of education, especially for progress achieved outside the school system. Therefore, the most effective leadership style in application to school organizations is the Transformational Leadership style. Transformational leaders are able to bring about change within each individual involved or for the entire organization to achieve higher performance. In an application to a transformational leader, he must have high charismatic, broad intellectual, and the ability to motivate his subordinates. This study uses a qualitative descriptive approach in the perspective of Max Weber's theory of authority. Weber explained that there are three types of authority in society. The First is the Legal Authority, the Second is the Traditional Authority, and the last is the Charismatic Authority. And from this 2 research, the leader in this school is more charismatic. Charisma is a very special leader. Weber sociologically describes charismatic as an acknowledgment of the followers of a leader, of a privilege. Weber said that charismatic leadership is a type of leadership that is qualified, special and superior, and it has become a validity that is recognized by subordinates. Leaders who have a charismatic authority model must also have a vision and mission that can inspire people or their subordinates. Keywords: Leadership, Transformational, Charismatic, School